2020
DOI: 10.32585/ags.v3i2.542
|View full text |Cite
|
Sign up to set email alerts
|

THE ABILITY OF Lactobacillus plantarum BSL IN REDUCING THE TISSUE DAMAGE OF LIVER AND SPLEEN IN RATS INFECTED BY Listeria monocytogenes ATCC 7644

Abstract: Lactobacillus plantarum BSL, previously isolated from Indonesian sauerkraut. In this study, we investigated the ability of L. plantarum BSL in reducing the tissue damage of liver and spleen in rats infected by Listeria monocytogenes ATCC 7644. Treatment group of rats received 0.5 mL culture suspension (109 CFU/mL) of L. plantarum BSL and control group received 0.5 mL of 0.85% w/v NaCl daily for nine days of experiment. Both groups were infected at 3rd day with 0.5 mL of suspension of L. monocytogenes (109CFU/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…[48,[84][85][86][87] It has been suggested that L. plantarum BSL can reduce liver damage by producing cytokines and antagonistic compounds, reducing the secretion of pro-inflammatory interleukin, and protecting against pathogens. [88,89] Bifidobacterium may contribute to the maintenance of gastrointestinal health, enhancement of barrier function, and immunomodulation. [90,91] Furthermore, S. thermophilus prevents inflammatory bowel disease through increased production of anti-inflammatory (IL-4, IL-5, IL-10) cytokines and reduced secretion of pro-inflammatory IL-1𝛽 and IFN-𝛾.…”
Section: Effect On Gut Microbiota Populationmentioning
confidence: 99%
“…[48,[84][85][86][87] It has been suggested that L. plantarum BSL can reduce liver damage by producing cytokines and antagonistic compounds, reducing the secretion of pro-inflammatory interleukin, and protecting against pathogens. [88,89] Bifidobacterium may contribute to the maintenance of gastrointestinal health, enhancement of barrier function, and immunomodulation. [90,91] Furthermore, S. thermophilus prevents inflammatory bowel disease through increased production of anti-inflammatory (IL-4, IL-5, IL-10) cytokines and reduced secretion of pro-inflammatory IL-1𝛽 and IFN-𝛾.…”
Section: Effect On Gut Microbiota Populationmentioning
confidence: 99%